2021
DOI: 10.1038/s41598-021-02845-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between ambient air pollution and perceived stress in pregnant women

Abstract: Air pollution may influence prenatal maternal stress, but research evidence is scarce. Using data from a prospective cohort study conducted on pregnant women (n = 2153), we explored the association between air pollution and perceived stress, which was assessed using the 14-item Perceived Stress Scale (PSS), among pregnant women. Average exposures to particulate matter with an aerodynamic diameter of < 2.5 µm (PM2.5) or < 10 µm (PM10), nitrogen dioxide (NO2), and ozone (O3) for each trimester and the enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…This susceptibility resulted more evident for women with a lower level of education. The association between PSS scores and PM 10 was stronger in the spring season and no associations were found concerning NO 2 exposure [46].…”
Section: Air Pollution and Maternal Stressmentioning
confidence: 68%
See 2 more Smart Citations
“…This susceptibility resulted more evident for women with a lower level of education. The association between PSS scores and PM 10 was stronger in the spring season and no associations were found concerning NO 2 exposure [46].…”
Section: Air Pollution and Maternal Stressmentioning
confidence: 68%
“…The main characteristics of included studies are shown in Table 1. Seven articles were prospective studies [42][43][44][45][46][47][48] and two were retrospective ones [49,50]. Four studies were conducted in the USA, the other five respectively in China, Republic of Korea, Taiwan, Mexico, and Turkey.…”
Section: Literature Retrieval and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Nuyts et al (2019) found no relation between exposure to NO 2 and perceived stress in older adults in Belgium. However,Lamichhane et al (2021) find this relation between exposure to pollution and prenatal maternal stress in South Korea, as doZhang et al (2021) in university students in China. Although efforts to study the effect of pollution on negative emotions in Latin America have been made, these studies have been mainly linked to emotions like «annoyance»(Melo et al 2015, Machado et al 2018, 2020, added to sporadic efforts on other emotions(Boso et al 2019, Bertanha 2021).…”
mentioning
confidence: 78%
“…Vasoconstriction occurs due to regular exposure to such ambient air that changes the normal hemodynamics of the patient; further, enhanced inflammation and raised prooxidative mediators were also reported due to the continuous exposure to ambient air (PM2.5). In a recent study, prenatal maternal stress was also reported to be associated with ambient air pollution [ 75 ].…”
Section: Reviewmentioning
confidence: 99%